Editorial: Embracing the Ethical and Transformative Role of AI in Education - Silva , Altieres de Oliveira; Janes, Diego dos Santos; Santos , Renan (Review of Artificial Intelligence in Education, 2024)
This editorial addresses the growing integration of artificial intelligence (AI) in education, highlighting the advancements, ethical challenges, and legal implications associated with this technology. The articles in this edition of the Review of Artificial Intelligence in Education provide a comprehensive analysis of how AI is transforming higher education, enhancing the quality of learning, and addressing issues related to academic integrity and ethics. The editorial explores themes such as the use of chatbots, AI platforms for assessment, the need for ethical governance in the application of AI in scientific research, and the development of robust legal frameworks to ensure the responsible use of these technologies in educational environments.